MOLECULAR IDENTIFICATION OF MODERATELY HALOPHILIC BACTERIA AND EXTREMELY HALOPHILIC ARCHAEA ISOLATED FROM SALTED SHEEP SKINS CONTAINING RED AND YELLOW DISCOLORATIONS - (:unkn) unknown (AMER LEATHER CHEMISTS ASSOC, 2015)
Salted hides or skins containing red and yellow discolorations have been examined for many years, but much less information is available about the isolation and molecular techniques for identifying moderately halophilic bacteria and extremely halophilic archaea on the salted sheep skins exhibiting these blotches. The deteriorated salted sheep skins were collected from a warehouse in Spain. Moderately halophilic bacteria and extremely halophilic archaea were isolated from these samples and molecular identification of these microorganisms were performed using 16S rRNA gene sequence analysis. Total cell counts of moderately halophilic bacteria and extremely halophilic archaea were found as 10(5)-10(8) CFU/g and 10(5)-10(7) CFU/g, respectively. According to comparative partial 16S rRNA gene sequence analysis, Alkalibacillus halophilus, Pseudomonas halophila, Acinetobacter johnsonii, Alkalibacillus salilacus, Salimicrobium salexigens, Marinococcus luteus and Staphylococcus equorum subsp. equorum belonging to moderately halophilic bacteria; and Halorubrum tebenquichense, Halorubrum saccharovorum, Halococcus dombrowskii, Halococcus qingdaonensis, Natrinema pellirubrum, Halococcus morrhuae, Halorubrum kocurii, Halorubrum terrestre, Halorubrum lipolyticum, Halostagnicola larsenii, Haloterrigena saccharevitans and Natrinema versiforme belonging to extremely halophilic archaea were isolated from these sheep skins. Alkalibacillus halophilus belonging to moderately halophilic bacteria and Halorubrum tebenquichense belonging to extremely halophilic archaea were found as the most common species on the skins. Among the moderately halophilic bacterial isolates, Acinetobacter johnsonii showed lipolytic activities. Among the extremely halophilic archaeal isolates, Halococcus dombrowskii, Halococcus morrhuae, Natrinema pellirubrum, Halorubrum lipolyticum showed proteolytic activity and Halococcus dombrowskii, Halorubrum lipolyticum, Haloterrigena saccharevitans, Natrinema versiforme showed lipolytic activity. Hair slip, red and yellow discolorations, slimy layers and bad odor were detected on the skin samples examined. This study confirmed that salted sheep skins were contaminated by preservation salt containing different proteolytic or lipolytic species of mostly extremely halophilic archaea. Therefore, antimicrobial applications during brine curing of skins should be applied to overcome halophilic microbial damage on the salted skins.
Keywords: SP-NOV.; XIN-JIANG; GEN-NOV; LAKE; PROPOSAL